Mediating the Voice of Social blogging: A Multimodal Analysis of an American Personal blog - Rosalba Rizzo (Culture e Studi del Sociale)
Social blogs and social blogging are terms used to describe second-generation Internet pub-lishing tools that blend features of both traditional blogging and social networking. The lines between blogging and social media continue to blur, making blogging more social, according to blog search engine Technorati?s report on why people blog. The weblog phe-nomenon raises a number of rhetorical issues, and one of the more intriguing of these is the peculiar intersection of the public and private that weblogs seem to determine. The confes-sional nature of blogs has redrawn the line between the private and the public dimensions of our lives and blogs can be both public and intensely personal in possibly contradictory ways. They are addressed to everyone and at the same time to no one and they seem to serve no immediate practical purpose, yet increasing numbers of both writers and readers are devoting increasing amounts of time to them. With an overview of the different definitions of the blogs, this study takes the reader through a journey of understanding the importance of blogs, how they work, who are the voices and who reads them.